1978
DOI: 10.1007/bf00441357
|View full text |Cite
|
Sign up to set email alerts
|

HLA frequencies and haplotypes in children with idiopathic thrombocytopenic purpura (ITP)

Abstract: 26 patients with an acute reversible ITP and 6 with chronic ITP were tissue typed, together with their healthy first-degree relatives. The HLA frequencies of the different groups were compared with those of a normal control population. The only significant difference between the groups was an increase in the frequency of Aw32 in acute ITP patients. HLA-Aw32 was present in 26.9% of patients, but in only 0.8% of the controls (corrected P = 0.000027). The possible importance of associations between antigens of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
1

Year Published

1981
1981
2010
2010

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 14 publications
(11 reference statements)
0
6
1
Order By: Relevance
“…The observed high frequency of HLA-A28 could be explained by chance; a similar observation has been reported [12], however. Our results do not confirm the previously reported increased incidence of HLA antigens HLA-B8, B12 [11], BW38 [12] and AW23 [19]. This may be due to regional differences in HLA frequencies or sampling error.…”
Section: Discussioncontrasting
confidence: 57%
“…The observed high frequency of HLA-A28 could be explained by chance; a similar observation has been reported [12], however. Our results do not confirm the previously reported increased incidence of HLA antigens HLA-B8, B12 [11], BW38 [12] and AW23 [19]. This may be due to regional differences in HLA frequencies or sampling error.…”
Section: Discussioncontrasting
confidence: 57%
“…In addition, the sample population for some of these studies was limited. Select studies that reported no HLA association with ITP found an HLA allele increased in the ITP population; however, when a correction of the p value for the number of antigens tested was done, the results became insignificant [12,16,19]. Therefore, a particular HLA allele may or may not be linked to ITP.…”
Section: Introductionmentioning
confidence: 77%
“…HLA alleles found to be associated with ITP include HLA-B8 and -B12 in adult patients with chronic ITP [11], Aw32 in children with acute ITP [12], and HLA-A28 in chronic ITP patients [13]. The presence of HLA-DRw2 was also significantly increased in ITP patients along with the co-occurrence of either A3 and B7 (known to be in linkage disequilibrium with DRw2) or A26 and Bw38 [14].…”
Section: Introductionmentioning
confidence: 93%
“…There is general agreement that associations between HLA antigens and nonmalignant diseases are due to the presence in the HLA complex of a susceptibility gene for a special disease in linkage disequilibrium with some HLA markers [5]. Striking associations with certain HLA antigens have especially been shown for diseases with immunopathogenic components [6,12,14]. For malignant diseases such associations, though extensively studied, are very rare.…”
Section: Discussionmentioning
confidence: 99%